Contralateral type of delayed endolymphatic hydrops may consist of two phenotypes based on a magnetic resonance imaging preliminary study. (2nd November 2017) - Fukushima, Munehisa; Yokoi, Kei; Iga, Junpei; Akahani, Shiro; Inohara, Hidenori; Takeda, Noriaki
Abstract: Objective: This study was performed to determine the volume distribution of EH in contralateral DEH. Patients and methods: Five contralateral DEH patients (age range = 21–77 years) and one ipsilateral DEH patient. Visualization of in vivo EH using 3T magnetic resonance (MR) imaging was performed by intravenous administration of gadolinium. The EH volume was determined quantitatively by adding the area of EH in consecutive MR images. Results: The total EH volume of the patients with contralateral DEH varied from 24.2 to 56.6 μL in the first ear and 20.2 to 35.7 μL in the contralateral ear. EH was dominantly developed in the first ear for Patient no. 3 and 4, and not dominantly developed in the first ear for Patient no. 1, 2, and 5. Conclusions: The volume distribution of endolymphatic hydrops (EH) in contralateral delayed endolymphatic hydrops (DEH) was classified into two phenotypes. This suggests that contralateral DEH may consist of two etiologies.